2019
DOI: 10.1111/jade.12231
|View full text |Cite
|
Sign up to set email alerts
|

Digital Work Practices: Affordances in Design Education

Abstract: This article draws from a multi‐disciplinary, multi‐institutional research project on digital work practices and graduate work readiness. Utilising the concept of technology affordances, we focus on the potential for domain‐specific learning experiences within design education. For the purpose of this project, we have articulated digital capabilities in design by adapting affordance categories in terms of three levels of complexity for scaffolded learning: functional, perceptual and adaptive. In order to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Aside from mastering computer graphics technically, there are also skills and ability to use that capacity as tools in design practice. This substantiates previous findings referring to the importance of digital capabilities should go far beyond functional knowledge and skill in using tools [49]. These findings suggest instruction for learning computer graphic needs to apply greater attention to contextual requirements; 1) student-centered, 2) have the current technology mindset, 3) focus on the design practice, and 4) flexible, ability to be easily modified to respond to circumstances or conditions.…”
Section: 3supporting
confidence: 88%
See 1 more Smart Citation
“…Aside from mastering computer graphics technically, there are also skills and ability to use that capacity as tools in design practice. This substantiates previous findings referring to the importance of digital capabilities should go far beyond functional knowledge and skill in using tools [49]. These findings suggest instruction for learning computer graphic needs to apply greater attention to contextual requirements; 1) student-centered, 2) have the current technology mindset, 3) focus on the design practice, and 4) flexible, ability to be easily modified to respond to circumstances or conditions.…”
Section: 3supporting
confidence: 88%
“…The basic skills of the traditional way to learning design are not enough, especially caused by the various needs of its users [48]. This finding has identified that, in establishing a professional graphic designer, design learning should place more consideration on design practice and understandings of the design process, rather than teaching specific technical tools or software that might be different or even changing future industry [49]. The finding suggested new learning objectives on learning computer graphic.…”
Section: Learning Objectives Based On Student Needsmentioning
confidence: 99%
“…Crosby, Pham, Peterson and Lee (2020) make similar findings. They report on roundtable discussions with ‘design experts from private practice, media, finance and private consulting practices’ (Crosby et al.…”
Section: Reforming Design Educationmentioning
confidence: 55%
“…Quality control, quality assurance, and comprehensive quality management are some of the fundamental elements of quality management (Dudin et al, 2017;Crosby et al, 2020). Applicable rules are implementing elementary and secondary education standards as part of the Quality Assurance System (QAS).…”
Section: Introductionmentioning
confidence: 99%